2022
DOI: 10.9756/int-jecse/v14i1.221139
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of VAR (Virtual Augmented Reality) based Educational Games in Harapan Bunda Islamic Kindergartens in Semarang City

Abstract: Due to the contemporary state of game - based learning, the advancement is so rapid that one criterion is that kindergarten children are active playing games on the side - lines of their parents' busy lifestyles; this is absolutely a chance to generate game - based learning that are tailored to the developmental level of kindergarten children, so that educational games are able to be produced. enhance kindergarten children's sensorimotor abilities since this technology may offer virtual and augmented reality t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This research has referred to several previous studies which showed that the augmented reality prototype introduction of the android-based solar system with the markerbased tracking method was able to increase students' learning motivation [5]. Then it was strengthened by the effective use of educational games based on virtual augmented reality in learning in kindergarten in the city of Semarang which showed that students and kindergarten teachers were very enthusiastic about participating in learning in a fun and fun way [6], then students were very enthusiastic about using textbooks. based on augmented reality which is able to display augmented reality in learning in schools [7].…”
Section: Introductionmentioning
confidence: 80%
“…This research has referred to several previous studies which showed that the augmented reality prototype introduction of the android-based solar system with the markerbased tracking method was able to increase students' learning motivation [5]. Then it was strengthened by the effective use of educational games based on virtual augmented reality in learning in kindergarten in the city of Semarang which showed that students and kindergarten teachers were very enthusiastic about participating in learning in a fun and fun way [6], then students were very enthusiastic about using textbooks. based on augmented reality which is able to display augmented reality in learning in schools [7].…”
Section: Introductionmentioning
confidence: 80%
“…The errors presented as the objective tobe revised prototype which validate on the next trials. The administered questionnaire illustrated the design flaw, and cloud-based storage delay (Handayani & Aprilliandari, 2022;Kurniasih et al, 2022).…”
Section: The Stages Of Processmentioning
confidence: 99%